EFFECTS OF EMS ON FOOT DROP ASSOCIATED WITH GRADE - Mirza Obaid Baig; Maimoona Yaqub (Journal of University Medical & Dental College, 2016)
ABSTRACT A 51 year old lady; known case of diabetes mellitus, post wound debridement i.e. 4 open wounds of grade III presented to us with foot drop, with prominent sensory deﬁcit over right lower leg/foot i.e. 0 on Nottingham scale for impaired sensation, marked pedal edema and 5/10 – 6/10 pain on VAS during day and night respectively, Wounds were poorly granulated and foul smelling. Physiotherapy sessions were planned including twice a day electrical muscle stimulation sessions, strategies to decrease edema and improve muscle action which resulted in noticeable improvement in motor and sensory ability, pain levels, edema and psychological status of patient. Thus, this study gives evidence of the effect of Electrical muscle stimulation in grade III open wounds associated with motor/sensory weakness post surgery.